Analisis Dalam Melakukan Optimalisasi Inovasi Kinerja Pegawai Serta Peran Jabatan Di Inspektorat Kabupaten Deli Serdang - Aisah, Mira Nur; Aslami, Nuri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to analyze the optimization of employee performance and the role of positions in the Deli Serdang Regency inspectorate. Competence of the employees (apparatus) of the Inspectorate is a variable which as a role determines the feasibility of a position held. Judging from several independent factors which become an educational background, technical competence, and job certification and of course training. The sample of this research is the employees (all) of the Inspectorate apparatus of Deli Serdang Regency, amounting to approximately 41 people. Currently under the leadership of Mr. H. Edwin Nasution. To test the optimization of employee performance and the role of positions in the Inspectorate Service of Deli Serdang Regency, this is done using the apprenticeship method. Well, it can also be done on a trip for approximately one month that has been done. The results of this study can be proven that in general terms the performance affects the position of each apparatus. Because, each level has each different performance power. Moreover, having different positions in the same office. There are Inspectors, Secretary, Head of General Sub-Section, Head of Program Sub-Section, Head of Evaluation and Reporting Sub-Section, Assistant Region I Inspector, Assistant Region II Inspector, Assistant Region III Inspector, and Assistant Region IV Inspector. Which in each section has a performance which of course varies according to the position according to the apparatus. It is also proven by around 75% who have become PNS (Civil Servants). Meanwhile, 25% are still in the honorary category. Therefore, this is the effect that occurs on performance and also the position.